PREVALENCE OF URINAR SCHISTOSOMIASIS AMONG PUPILS ATTENDING ANGWAN LAMBU PRIMARY SCHOOL, KEFFI, NASARAWA STATE, NIGERIA - Abdullahi, Mairiga; Ramatu, M. A. (FUDMA JOURNAL OF SCIENCES, 2023)
This research aims to investigate the prevalence of urinary tract schistosomiasis among pupils of Angwan Lambu Primary School in Keffi Local Government Area of Nasarawa State conducted from June to September 2021. One hundred and fifty (150) urine samples were collected from the pupils and brought to the laboratory for parasitological examination of schistosome eggs using sedimentation method. The overall prevalence of schistosomiasis was 23(15.33%). The prevalence of urinary schistosomiasis was significantly higher (P > 0.05) in male 15(10%) than the female 8(5%). There was no significant association (P > 0.05) in the prevalence of urinary infection between genders and age.  The results of the study showed highest prevalence in age group 7-9 (6%) followed by age group 10-12 (5%) while the lowest prevalence was observed among age group 4-6 (2%) which revealed the prevalence of S. haematobium in the study area. Therefore, periodic chemotherapy of the affected populations with praziquantel, improved health education, provision of portable water, adequate sanitation and control of fresh water snails will reduce the risk of morbidity and disease transmission in the area
Keywords: Prevalence; schistosomiasis; sedimentation; transmission; praziquantel; school